1999
DOI: 10.1063/1.478545
|View full text |Cite
|
Sign up to set email alerts
|

A molecular theory of the homogeneous nucleation rate. I. Formulation and fundamental issues

Abstract: A molecular theory of the rate of homogeneous vapor phase nucleation is formulated. The ultimate goal is a theory that contains no ad hoc assumptions or arbitrary parameters having magnitudes that must be assigned in an ad hoc manner. The centerpiece of the theory is a defined cluster denoted as the n/v-Stillinger cluster, a hybrid that combines the original Stillinger cluster and the more recent n/v cluster. The Stillinger component assures that redundancy is avoided in the characterization of the cluster and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(61 citation statements)
references
References 69 publications
0
61
0
Order By: Relevance
“…Since typically the density of ions involved in the cloud-chamber experiments is extremely low, it is reasonable to assume that a cluster contains one ion at most. Intercluster interactions can also be neglected [21,23]. Maximizing the partition function of the supersaturated vapor gives the most probable cluster size distribution n w …”
Section: (Received 7 June 2000)mentioning
confidence: 99%
See 2 more Smart Citations
“…Since typically the density of ions involved in the cloud-chamber experiments is extremely low, it is reasonable to assume that a cluster contains one ion at most. Intercluster interactions can also be neglected [21,23]. Maximizing the partition function of the supersaturated vapor gives the most probable cluster size distribution n w …”
Section: (Received 7 June 2000)mentioning
confidence: 99%
“…This MC method is based on the physical cluster theory [21]; namely, a supersaturated vapor is viewed as a mixture of physical clusters, and a configuration of supersaturated vapor is described by the cluster-size distribution ͕n w i , n s i ͖, where n w i and n s i are the number of clusters containing i molecules, and 0 and 1 ion, respectively. The total number of ion-containing clusters is N s P i 0 n s i .…”
Section: (Received 7 June 2000)mentioning
confidence: 99%
See 1 more Smart Citation
“…More sophisticated treatments, such as the n/v-Stillinger cluster introduced by Reiss and co-workers, are rather complex. An excellent review of recent progress in this area and the application of these ideas to nucleation theory is provided by Senger et al [15].…”
Section: Introductionmentioning
confidence: 99%
“…Only the largest cluster in the simulation box is regarded as the cluster, smaller entities that satisfy the Stillinger definition are considered to be part of the surrounding vapour. It has been shown that a small variation of Stillinger radius in the neighbourhood of 1:5s does not lead to a significant change in the cluster equilibrium size distribution [4,25].…”
Section: Methodsmentioning
confidence: 99%